Increased sensitivity of microbiological testing of cornea organ culture medium by additional resin treatment. Issue 1 (10th November 2018) - Skenderi, Zemra; Giurgola, Laura; Gatto, Claudio; D'Amato Tóthová, Jana; Pruß, Axel; Schroeter, Jan
Abstract : Objective: This validation study investigates the treatment of cornea organ culture medium (Modified Eagle Medium, Biochrom GmbH, Berlin, Germany) with RESEP, a new medical device for antibiotics removal, before microbiological testing with BACTEC TM blood culture bottles. Methods and analysis: 10–100 colony forming units of Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Bacillus subtillis, Aspergillus brasiliensis, Clostridium sporogenes, Enterobacter cloacae and Staphylococcus epidermidis were inoculated in 9mL of cornea organ culture medium. In group A, the medium was withdrawn with RESEP and treated for 20 min at room temperature, and then inoculated in BACTEC Plus Aerobic/F/Anaerobic/F blood culture bottles. In group B, the medium, spiked by the inoculation of microorganism, was injected directly. For each strain, a growth control was performed, by direct inoculation of the microorganisms in BACTEC TM vials (positive control). All samples were incubated in the automated BACTEC TM blood culture system at 36°C ±1°C for maximum of 14 days or until a positive reading. The elimination of antibiotics from the medium by RESEP was determined by high-performance liqiud chromatography. Results: After 20 min of RESEP treatment, 100% (n=9) of streptomycin, 100% (n=9) of amphotericin B and 99.7% (n=9) of penicillin G were eliminated. In group A, all microorganisms were detected within 3 days of incubation with a sensitivity of 100% (n=99) and showed no significant delay compared with the positive controls. In group B, the overall sensitivity was 67.9% (n=96) with a significant delay until detection of microbial growth for all tested microorganisms except for A. brasiliensis . Conlclusion: The use of RESEP to eliminate the antibiotics from cornea organ culture medium increases the sensitivity of the microbiological testing with BACTEC TM Plus blood culture bottles significantly and fulfils the requirements of the European Pharmacopoeia method suitability test.